Feast for the eyes: How demographics and psychographics shape Food Porn appeal in culinary tourism - Boro, Sunita; Dixit, Saurabh Kumar (Hotel and Tourism Management, 2025)
Purpose – This study aims to understand how culinary tourism in Assam is contributing to boost its tourist influx following Covid-19. Methodology – The study here is descriptive in its approach and utilises both primary and secondary sources of data. The research adopts an empirical approach, surveying 398 tourists visiting the state using a structured questionnaire. Findings – Mean score analysis shows that these tourists do not initially consider food as a primary factor of when choosing a travel destination. A regression model was developed to assess the impact of psychographic variables on consumer responses to food imagery. Beliefs showed the highest impact, meaning that tourists who actively explore local food during travel are particularly responsive to the state’s food-related experiences. The role of demographics is also evident as the influence caused by food imagery varies significantly gender, age group, income, and education. Implications – The study highlights how tourists’ values and experiences regarding local food and community help creating an inclination towards experiencing the local culture, which can lead to a heightened – influence of Food Porn and increased tourist influx.